Behind the Devotion: Structural Exploitation of Teachers in Private and Foundation Schools - Winarsih, Nining; Rindi, Asih (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This study examines the paradox of devotion and exploitation among teachers in private and foundation schools in rural Indonesia. Although teachers are often portrayed as moral exemplars devoted to their profession, their lived experiences reveal a reality of economic precarity, structural inequality, and institutional neglect. The research aims to explore how religious and moral values intersect with structural exploitation and how such values shape teachers’ motivation and endurance despite material deprivation. Using a qualitative descriptive approach with a case study design, data were collected through in-depth interviews and field observations with honorary teachers at a private Islamic foundation in Krucil, Probolinggo. The findings indicate three key patterns: (1) low salary and structural inequality, in which teachers receive compensation far below the regional minimum wage; (2) religious and moral motivation, where values of ikhlas (sincerity) and pengabdian (devotion) serve as coping mechanisms that transform injustice into moral virtue; and (3) infrastructural limitations, which further intensify teachers’ vulnerability while reinforcing the narrative of sacrifice. This research reveals that religious devotion functions as a double-edged moral economy, providing psychological strength while simultaneously legitimizing exploitation. The study shows how devotion operates as an ideological tool that normalizes inequality and suppresses resistance. This research contributes to how moral and religious discourses sustain labor precarity in the teaching profession. It argues that teacher welfare must be addressed not only through material reform but also through cultural and ideological transformation. Devotion should no longer serve as a justification for inequality but as a moral foundation for justice, dignity, and educational reform